1994
DOI: 10.1111/j.1365-2494.1994.tb01976.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of sugar beet pulp‐based silage additives on effluent production, fermentation, in‐silo losses, silage intake and animal performance

Abstract: First-harvest direct-cut, double-chopped grass (190 and 164gDMkg~'

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
10
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 9 publications
4
10
0
Order By: Relevance
“…The lowest pH was found out in experimental silage made of pressed sugar-beet Table 1 pulp treated with KEM preservative in the dose of 6 l/t (3.66 ± 0.01). These data are in agreement with results published by Moore and Kennedy (1994). The application of KEM corroborated the statement published by Baintner et al (1983), who observed that a combination of organic acids strengthened the synergic effect, decreased the pH value and improved the bactericidal effect of additives.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The lowest pH was found out in experimental silage made of pressed sugar-beet Table 1 pulp treated with KEM preservative in the dose of 6 l/t (3.66 ± 0.01). These data are in agreement with results published by Moore and Kennedy (1994). The application of KEM corroborated the statement published by Baintner et al (1983), who observed that a combination of organic acids strengthened the synergic effect, decreased the pH value and improved the bactericidal effect of additives.…”
Section: Resultssupporting
confidence: 92%
“…and accounted only for 20.91% and 31.58%, resp., of all acids. These results corresponded with data published by O'Kiely (1992) and Moore and Kennedy (1994), who observed a marked decrease in production of VFA, LA, ammonia and alcohol after the application of formic acid as an additive into the experimental silages. The regression analysis of the effects of different concentrations of chemical preservatives on the total production of fermentation acids (and/or LA) revealed a very close linear relationship between the dependent and independent variables.…”
Section: Resultssupporting
confidence: 91%
“…Conversely, in this study, as ground corn was added to the cabbage, its moisture-absorption capacity decreased (0.82, 0.71, 0.65, 0.69, and 0.68 g of moisture per gram of ground corn added at 200, 300, 400, 500, and 600 g kg -1 of cabbage, respectively). Normally other products like citrus and beet pulp are used as an additive for grass silages due to their high capacity to absorb moisture and high WSC content, respectively (Moore and Kennedy, 1994;Bernardes et al, 2005). However, the use of a starch-rich source (i.e., ground corn) seems more appropriate for diets used in the ruminant and monogastrics nutrition aiming to reduce costs associated with animal feeding.…”
Section: Discussionmentioning
confidence: 99%
“…There are conflicting data in the literature regarding the effect of molasses on N concentration of silage. Some researchers reported that the addition of molasses to silage increased the N concentration of silages (Lattemae et al, 1985;Kennedy, 1990;Baytok et al, 2005), others did not observe an effect (Spoelstra et al, 1990;O'Kiely 1992;Van Niekerk et al, 2007) while some reported a decrease in the N concentration of silages (Moore & Kennedy, 1994). In this study molasses…”
Section: The South African Journal Of Animalmentioning
confidence: 50%